Chitosan edible coating: a potential control of toxic biogenic amines and enhancing the quality and shelf life of chilled tuna filets - Elsabagh, Rasha; Ibrahim, Samar S.; Abd-Elaaty, Elsayed M.; Abdeen, Ahmed; Rayan, Ahmed M.; Ibrahim, Samah F.; Abdo, Mohamed; Imbrea, Florin; Şmuleac, Laura; El-Sayed, Amal M.; Abd Elghaffar, Rasha Y.; Morsy, Mohamed K. (Frontiers in Sustainable Food Systems, 2023)
Edible films and coatings offer great potential to support sustainable food production by lowering packaging waste, extending product shelf life, and actively preserving food quality. Using edible coatings containing plant extracts with antioxidant and antibacterial characteristics could help to enhance the quality and shelf life of fish products. In this study, the combination effect of chitosan with beetroot, curcumin, and garlic extracts on biogenic amines (BAs) reduction, biochemical quality [pH, thiobarbituric acid index (TBA), trimethylamine (TMA), and total volatile base (TVB)], shelf life and sensory characteristics of tuna filets was investigated over 14 days of refrigerated storage compared to control (uncoated) samples. The results showed that the coated samples experienced a lower increase in BAs levels than the control samples. Among the treated samples, chitosan incorporated with curcumin (CH-C) showed the highest reduction in BAs formation (1.45 – 19.33, 0.81 – 4.45, and 1.04 – 8.14 mg/kg), followed by chitosan with garlic (CH-G) (1.54 – 21.74, 0.83 – 5.77, and 1.08 – 8.84 mg/kg), chitosan with beetroot extract (CH-B) (1.56 – 31.70, 0.84 – 6.79, and 1.07 – 10.82 mg/kg), and chitosan without extract addition (CH) (1.62 – 33.83, 0.71 – 7.82 and 1.12 – 12.66 mg/kg) compared to control samples (1.62 – 59.45, 0.80 – 11.96, and 1.14 – 20.34 mg/kg) for histamine, cadaverine, and putrescine, respectively. In addition, the rate of increase in pH, TBA, TMA, and TVB of all coated treatments was lower than in the control samples. Sensory evaluation results revealed that chitosan-treated samples incorporated with beetroot, garlic, and curcumin extracts showed good quality and acceptability characteristics. Overall, chitosan edible coatings incorporated with beetroot, garlic, and curcumin extracts reduced the formation of biogenic amine, delayed biochemical deterioration, and extended the shelf life of tuna filets. Among the treated samples, CH-C demonstrated a remarkable superiority in all the studied parameters. Therefore, this study provides a promising strategy for the incorporation of active compounds in edible coatings to improve the quality and safety of foods during storage.